PU/lignocellulosic composites produced from recycled raw materials - Gama, Nuno (2022)
Lignocellulosic composites are biodegradable, have low cost, neutrality to CO2 emission, easily processed, easily available and pause no health risks, therefore these materials have been the subject of an increase of interest. In addition, there is a continuous demand of materials obtained from renewable resources and waste recycling. In that sense, in this study polyurethane (PU) residues were mixed with residues of cork and pine (up to 70 wt/wt) to produce 100% recycled composites. Cork is well known to be a light and a thermal insulator material, so the addition of cork granulates decreased both density (circa 51%) and thermal conductivity (circa 61%) of the composites. In turn, pine fibers are hydrophilic and have cylindrical shapes, thus their presence increased the water absorption and improved the mechanical properties of the composites. From the results, these composites proved to be suitable to be used as structure and thermal insulation materials with the advantage of being produced from 100% recycled raw-materials.